Innovative cutting materials for finish shoulder milling Ti-6A1-4V aero-engine alloys - Oosthuizen, G. A. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2009.